Gesellschaft in der Zerstreuung Soziale Ordnung und Konflikt im frühneuzeitlichen Graubünden - Liniger, Sandro (Bedrohte Ordnungen, 2017)
Despite established social, political and cultural differences, and despite the tricky mountainous setting, over 50 early modern era alpine valley communities managed to cooperate reliably with one another without either central instance or state. Notwithstanding these adverse conditions - such as steep mountains, remote valleys and settlements strewn far apart - they were able to successfully organise their common social and political interests. They even developed a dynamic unity and order completely without superior central power. This at first seemingly paradoxical finding is taken by Sandro Liniger as an opportunity to analyse just how such a dispersed society functions: Which specific logic characterises such an alternative form of organising common social and political life? Which instabilities and resistances are peculiar to it? And which conflicts characterise it?